From infrastructure to digital networks: accessibility and connectivity in transport geography research at Aberdeen. (2nd October 2019) - Beecroft, Mark; Cottrill, Caitlin D.; Farrington, John H.; Nelson, John D.; Niewiadomski, Piotr
ABSTRACT: This paper considers the contribution made to transport geography research at the University of Aberdeen over the last century. In section one, the earliest work in transport geography emphasised the physical connectivity provided by transport through infrastructure networks. Section 2 discusses the contribution made at Aberdeen to debates around accessibility and connectivity. This work had a strong rural dimension and evidenced a growing recognition of the importance of technology in transport. It provided the springboard for research on digital connectivity with important contributions to the wider domain of transport studies in the fields of flexible transport, rural connectivity, transport and energy and social media and big data as reported in Section 3. Section 4 brings the story of transport research at Aberdeen up to the present. It frames research under the banner of intelligent mobility (IM), which links technology and mobility to the wider societal objective of enabling the smarter, greener and more efficient movement of people and goods. Contributions are reported to the fields of shared mobility, smart rural mobility, transport security and privacy and accessibility. Finally, a return to the theme of infrastructure networks and connectivity is highlighted in work on global production networks in aviation.